Comprehensive bioinformatics analysis was used to identify and verify differentially expressed genes in targeted therapy of colon cancer - Jialin Zhang; Xinyu Wang; Zhen Li; Ziqiang Wang; Xiaona Hao; Yuyun Li; Yingjie Zhang (Scientific Reports)
Abstract Colorectal cancer (CRC) is one of the most common malignant tumors. CLCA1 and ZG16 are lowly expressed in CRC, and we wanted to investigate whether they could be prognostic biomarkers for the malignant progression of CRC. 12,195 DEGs and 12,071 DEGs were identified through the GSE39582 dataset and TCGA dataset, and then 50 coexisting genes were selected for further analysis using Venn diagrams. These 50 DEGs were then subjected to GO and KEGG functional enrichment analyses, along with genome-wide GSEA. the first 5 core genes were identified and visualized using Cytoscape through the PPI network. Then the expression of ZG16 and CLCA1 in normal and tumor tissues were analyzed using GSE39582 and TCGA datasets, and correlation analysis, and survival analysis were performed. The expression of ZG16 and CLCA1 in CRC cells was verified by qRT-PCR, and cell proliferation, migration, and invasion abilities were detected by CCK-8, scratch assay, clone formation assay, and Transwell assay. The expression levels of ZG16 and CLCA1 were significantly lower in CRC tissues than in normal tissues. Survival analysis showed that low expression of ZG16 and CLCA1 was associated with poor survival outcomes. Multifactorial analysis showed that low expression of ZG16 and CLCA1 was an independent risk factor affecting tumor prognosis. Cellular experiments showed that cell proliferation, migration, and invasion were inhibited after overexpression of ZG16 and CLCA1. Correlation analysis showed that ZG16 and CLCA1 expression levels were positively correlated and the correlation was statistically significant. GSEA enrichment analysis based on CLCA1-related genes and ZG16-related genes (FDR < 0.25, P < 0.05) revealed that the related genes of both genes were closely related to the GnRH signaling pathway. CLCA1 and ZG16, which are lowly expressed in CRC tissues, are associated with poor prognosis of CRC and may be one of the markers for diagnostic screening and prediction of prognostic outcome in CRC. Meanwhile, CLCA1 and ZG16 may also be new targets for tumor immunotherapy.